2023
DOI: 10.3390/nu15224823
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Polyphenols—Natural Bioactive Compounds with Potential for Preventing and Treating Some Allergic Conditions

Anna Dębińska,
Barbara Sozańska

Abstract: In light of the constantly increasing prevalence of allergic diseases, changes in dietary patterns have been suggested as a plausible environmental explanation for the development and progression of these diseases. Nowadays, much attention has been paid to the development of dietary interventions using natural substances with anti-allergy activities. In this respect, dietary polyphenols have been studied extensively as one of the most prominent natural bioactive compounds with well-documented anti-inflammatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 309 publications
0
2
0
Order By: Relevance
“…Polyphenols can serve as a substitute for conventional corticosteroid and antihistamine treatments. They possess anti-allergic characteristics, including the capacity to inhibit the synthesis of proinflammatory cytokines and leukocytes, as well as the secretion of histamine [ 69 ]. Polyphenols have shown the capacity to regulate the balance between T helper (Th)1/Th2 and impede the generation of antigen-specific IgE antibodies.…”
Section: Polyphenols and Their Importance To Skin Healthmentioning
confidence: 99%
“…Polyphenols can serve as a substitute for conventional corticosteroid and antihistamine treatments. They possess anti-allergic characteristics, including the capacity to inhibit the synthesis of proinflammatory cytokines and leukocytes, as well as the secretion of histamine [ 69 ]. Polyphenols have shown the capacity to regulate the balance between T helper (Th)1/Th2 and impede the generation of antigen-specific IgE antibodies.…”
Section: Polyphenols and Their Importance To Skin Healthmentioning
confidence: 99%
“…Polyphenols are a diverse category of more than ten thousand chemical compounds that are naturally found in plants. They are produced as secondary metabolic products in response to free radicals or environmental stress factors [ 20 , 27 ]. Phenolic chemicals serve multiple functions in plants, including defense against pathogens, protection against oxidative damage, acting as light sensors, influencing sensory qualities, and regulating growth and reproduction [ 28 ].…”
Section: Polyphenols and Their Characteristicsmentioning
confidence: 99%
“…These compounds are found in significant quantities in kale, onion, tomato, apples, berries, herbal tea, and red wine [ 32 ]. Additional significant flavonoids in the diet include isoflavones, which can be found in soybeans; anthocyanidins, which are present in colored vegetables and fruits such as red cabbage, eggplant, berries, and cherries; catechins, which are found in high concentrations in green tea, red wine, and dark chocolate [ 20 ]; flavones such as apigenin, luteolin, and baicalin, which are abundant in green and black tea, cereals, and aromatic herbs like celery and parsley [ 20 ]; and naringenin and hesperidin, which are phenolic acids, such as gallic, caffeic acid, and ferulic acid, make up almost 30% of the overall polyphenols in our diet [ 20 ]. These acids can be found in red fruits, onions, and black radishes [ 27 ].…”
Section: Polyphenols and Their Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In light of the increasing prevalence of allergic diseases, researchers' attention has focused on the role of diet in their prevention. The literature data indicate that quercetin has high anti-allergic potential and can be used in the prevention or treatment of allergic diseases such as allergic rhinitis, allergic asthma, and atopic dermatitis [12][13][14]. In a clinical study on patients with allergic rhinitis in the sensitization phase, it was observed that the use of oral quercetin (200 mg/day) for 4 weeks relieved symptoms such as itchy eyes, sneezing, nasal discharge, and sleep disturbances, compared with the placebo group [15].…”
Section: Introductionmentioning
confidence: 99%